Pengaruh Gaya Kepemimpinan dan Disiplin Guru terhadap Kinerja Pengajar SD di Kecamatan Kayuagung - Yuli Husnita Putri; Tri Widayatsih; Mahasir Mahasir (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to determine (1) The influence of principal leadership on the performance of elementary school teachers. (2) The influence of work discipline on the performance of elementary school teachers. (3) The influence of principal leadership and work discipline on the performance of elementary school teachers. This study is a quantitative study with data collection techniques using questionnaires. The hypothesis was tested using multiple linear regression analysis. The population in this study was 158 teachers in Cluster III in Kayuagung District, Ogan Komering Ilir Regency. The techniques used in data collection used questionnaires and documentation. Data analysis techniques and prerequisite tests consisting of normality tests, linearity tests, multicollinearity tests, and heteroscedasticity tests. For hypothesis testing using simple linear regression analysis, multiple linear regression, R test, t test, and F test. The results of the study indicate that (1) There is a significant positive influence of principal leadership on teacher performance in Cluster III in Kayuagung District, Ogan Komering Ilir Regency, this can be seen from the results of the t test obtained t count of 0.414 with a significance value of 0.001 <0.05 (2) There is a significant positive influence of teacher discipline on teacher performance in Cluster III in Kayuagung District, Ogan Komering Ilir Regency, this can be seen from the results of the t test obtained t count of 0.268 with a significance value of 0.000 <0.05. (3) There is a simultaneous/joint influence between principal leadership and teacher discipline on teacher performance in Cluster III in Kayuagung District, Ogan Komering Ilir Regency, this can be seen from the results of the simultaneous test obtained 0.005 <0.05. This means that there is a significant influence simultaneously or together between the independent variables on the dependent variable.